2014
DOI: 10.1016/j.imbio.2013.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant effects of mannose-binding lectin ligands on the immune response to infectious bronchitis vaccine in chickens with high or low serum mannose-binding lectin concentrations

Abstract: Mannose-binding lectin (MBL) plays a major role in the immune response as a soluble pattern-recognition receptor. MBL deficiency and susceptibility to different types of infections have been subject to extensive studies over the last decades. In humans and chickens, several studies have shown that MBL participates in the protection of hosts against virus infections. Infectious bronchitis (IB) is a highly contagious disease of economic importance in the poultry industry caused by the coronavirus infectious bron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…For mammalian MBL, direct virus neutralization through interaction with viral glycoproteins, thereby blocking virus binding to receptors on host cells, has been described before (Brown et al, 2010;Ip et al, 2005;Ji et al, 2005;Zhou et al, 2010). Here, we observed that rcMBL binds two IBV strains, IBV-Beaudette and IBV-M41, in line with a previous observation with an unspecified IBV strain (Kjaerup et al, 2014a). As spike proteins of all other IBV strains are, while diverse in sequence, heavily glycosylated (with approximately 30 predicted N-linked glycosylation sites), it is expected that rcMBLs antiviral activity extends beyond IBV geno-or serotypes.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…For mammalian MBL, direct virus neutralization through interaction with viral glycoproteins, thereby blocking virus binding to receptors on host cells, has been described before (Brown et al, 2010;Ip et al, 2005;Ji et al, 2005;Zhou et al, 2010). Here, we observed that rcMBL binds two IBV strains, IBV-Beaudette and IBV-M41, in line with a previous observation with an unspecified IBV strain (Kjaerup et al, 2014a). As spike proteins of all other IBV strains are, while diverse in sequence, heavily glycosylated (with approximately 30 predicted N-linked glycosylation sites), it is expected that rcMBLs antiviral activity extends beyond IBV geno-or serotypes.…”
Section: Discussionsupporting
confidence: 92%
“…Chicken MBL seems to be important for shaping both the innate and the adaptive immune response for IBV (Hamzic et al, 2016;Juul-Madsen et al, 2011;Kjaerup et al, 2014b). Chickens with relatively high concentrations of cMBL appeared to clear IBV quicker and showed reduced viral titers in trachea compared to chickens with low cMBL levels (Juul-Madsen et al, 2011;Kjaerup et al, 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, a recent study in chickens has successfully explored a vaccine preparation that contains an MBL ligand able to inhibit MBL binding and activation of the lectin pathway of complement, in order to achieve a sufficient antibody response after vaccination [33]. A similar approach would certainly be feasible in humans in addition to systemic inhibition of MBL by recombinant human C1 inhibitor [34].…”
Section: Discussionmentioning
confidence: 99%
“…Receptors such as the toll-like receptor (TLR) 3, TLR7, and TLR2/6 may initiate the local trachea innate immune response upon IBV recognition (21,57). Since mannosebinding lectin (MBL) binds to IBV (36), early events in the immune response to IBV infection may involve MBL by opsonization of free virions, by complement activation at mucosal sites, or by inhibition of the virus entry through sialic acid-dependent receptors (21,31,32,47,63). In mammals, the complement system has been suggested to be important in T-cell activation together with the production of types I and II interferons (IFNs) and other mediators, which trigger the antiviral state of neighboring cells and the influx of T cells to the local tissue (35).…”
Section: Introductionmentioning
confidence: 99%